Eastern philosophy - Thompson Mel (London: Hodder & Stoughton Ltd, 2003)
"Eastern philosophy is an informative and entertaining three-part program that discusses the topics of spiritual enlightenment and religious thought. The series poses questions such as: Does God exist?, How can a person live a life of virtue? and examines it in relation to religion and spirituality. It explores the genesis of spiritual thought and investigates the central doctrines of Confucianism, Shinto, Hinduism, Judaism, and Islam"--Container.
Keywords: Philosophy, Asian; Religions